Their Barcelona baby bombshell - Douglass, Traci (Harlequin medical romance, 2022)
"Paramedic Isabella Rivas doesn't do commitment and entanglement. She had enough of that raising her five siblings after their mother died. But one red-hot night with a sexy stranger doesn't count, right? Except that single passionate encounter results in an unexpected pregnancy! And when she meets Carlos Martinez's familiar guarded eyes over a patient in the ER, she realizes that life has just got a whole lot more complicated ..."--Back cover.